2022
DOI: 10.1007/s11224-022-02029-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of [3H]diazepam derivatives as allosteric modulators of GABAA receptor α1β2γ2 subtypes: combination of molecular docking/dynamic simulations, pharmacokinetics/drug-likeness prediction, and QSAR analysis

Abstract: In this paper, a data set of [ 3 H] diazepam derivatives was analyzed using various computational methods: molecular docking/dynamic simulations, and QSAR analysis. The main aims of these studies are to understand the binding mechanisms by which benzodiazepines allosterically modulate GABA A receptor α 1 β 2 γ 2 subtypes, from inducing neuronal inhibition at lower doses to the anesthetic effect at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Finally, the 3LE0-Compound 8, 4N82-Compound 8, and 3AIC-Compound 8 complexes retain their stabilities in the last intervals (between 800 and 1500 ps, between 400 and 1500 ps, and between 900-1500 ps, respectively) (Figure 5a, b, and c). On the other hand, all the studied complexes exhibit higher stability, confirmed by MD simulations, because they maintained almost the same types of interactions compared to the molecular docking studies, which was also confirmed by the stability of the potential energy as a function of time (Figure 5a, b, and c), as reported in recent papers [73,74].…”
Section: Molecular Dynamics Simulationsupporting
confidence: 84%
“…Finally, the 3LE0-Compound 8, 4N82-Compound 8, and 3AIC-Compound 8 complexes retain their stabilities in the last intervals (between 800 and 1500 ps, between 400 and 1500 ps, and between 900-1500 ps, respectively) (Figure 5a, b, and c). On the other hand, all the studied complexes exhibit higher stability, confirmed by MD simulations, because they maintained almost the same types of interactions compared to the molecular docking studies, which was also confirmed by the stability of the potential energy as a function of time (Figure 5a, b, and c), as reported in recent papers [73,74].…”
Section: Molecular Dynamics Simulationsupporting
confidence: 84%
“…On the other hand, the major GABA A receptor isoform is made up of two α-subtypes, two β-subtypes, and one γ-subtype, or one δ-subtype. In the adult brain, 90% of GABA A receptors are γ-containing receptors, which are mostly distributed in synaptic locations [ 16 ]. However, it is generally accepted that the primary mature isoform consists of α1, β2, and γ2 subunits, which are positioned as γ2β2α1β2α1 counterclockwise around a central pore when observed from the outside of the cell [ 17 ].…”
Section: Introductionmentioning
confidence: 99%